Buoyant Agglomeration of the VAT Refund: An Application of EFA and CFA - Kumar, Sunil; Bagga, Tejwant Singh (Indian Journal of Finance, 2014)
Agglomeration of the VAT refund is a major flaw in the VAT system which certainly pushes the future of the industry into the dark and also unnecessarily harasses the industrial units because a lot of funds are blocked in the form of refund with the government, which otherwise could be invested in business. The manufacturer needs to pay input VAT when the raw materials are bought, and it is realized till the goods are disposed-off. Under the preview of the VAT system, the dealers either setoff the input VAT against the output VAT or lodge a claim with the government for the excess input VAT. The present research work tries to explore and confirm the factors responsible for the delayed VAT refund. Five factors are extracted which were accountable for the agglomeration of the VAT refund. Conceptual factors were found to be the main factor responsible for the delayed VAT refund. The refund mechanism under the VAT regime is not very effective not only in our country, but also in the neighboring countries where the VAT system has been adopted. The second and third major factors responsible for the delayed VAT refund are ’Fraud and Tax Evasion’ and ’Interstate VAT Divergence’ respectively. However, the foremost objective of the VAT implementation by almost all the countries in the world is to cope with the unwanted leakage of taxes in the form of fraud and tax evasion. VAT is used as a tool to bring harmony in the taxation system of the countries. However, it could not bring uniformity in India; rather, it has caused divergence in the volume of the VAT refund in the states.